Mesiodistal Crown Dimensions of the Permanent Dentition in a Nigerian Population - Emmanuel O. Ajayi; Yetunde O. Ajayi; Helen O. Oboro; Nneka M. Chukwumah (Dental Anthropology Association, 2010)
Mesiodistal crown dimensions of the permanent dentition were assessed in a Nigerian population. The study sample consisted of 54 dental casts of Nigerian subjects (33 males; 21 females) with a mean age of 26.6 (sd = 2.1) years. The subjects had their permanent teeth present and fully erupted from first molar to first molar, no interproximal caries or restorations and no abnormal tooth sizes or shapes. Descriptive statistics are provided. Sex differences in the means and comparisons with the means from other population were evaluated using t-tests. Results revealed no statistically significant difference in mesiodistal crown dimensions between the sexes and no left to right side tooth size discrepancy in the sample. The study provides normative data on the mesiodistal crown dimensions of Nigerian subjects. Compared to African Americans, crown dimensions tended to be smaller in these Nigerians, especially in males.